A review of the genus Afrasura Durante, 2009 from São Tomé Island with descriptions of a new species and a new subspecies (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V.; László, Gyula M. (Zootaxa, 2018)
Present paper contains a review of the lithosiine genus Afrasura Durante, 2009 from São Tomé Island (Democratic Republic of São Tomé and Príncipe). One new species, A. pectinatissima Volynkin & László, sp. nov. and one new subspecies, A. discocellularis saotomensis Volynkin & László, ssp. nov. are described. Asura thomensis Rothschild, 1913 is synonymized with Afrasura hieroglyphica (Bethune-Baker, 1911) widely distributed in West Africa. A new combination is established: Afrasura friederikae (Kühne, 2007), comb. nov. Adults, male and female genitalia of all species mentioned are illustrated.